2009
DOI: 10.1016/j.pain.2008.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Neuroactive steroids inhibit spinal reflex potentiation by selectively enhancing specific spinal GABAA receptor subtypes

Abstract: Recently, we demonstrated a spinal GABA(A) receptor (GABA(A)R)-dependent inhibition on the induction of repetitive stimulation-induced spinal reflex potentiation. However, it remains unclear whether steroid hormones modulate such an inhibition. Here, we show that progesterone is capable of producing GABA(A)Rs-dependent inhibition of the induction of spinal reflex potentiation by actions through neurosteroid metabolites. Progesterone (5mg/kg, twice daily for 4 days) up-regulates the expression of GABA(A)R alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…Based on the preclinical data on gaboxadol demonstrating a hypnotic profile in rats (Thakkar et al, 2008) and that the effects of the drug on EEG were blunted in d 0/0 mice (Winsky-Sommerer et al, 2007), it was pursued as a novel treatment for insomnia, reaching phase III clinical development (Wafford and Ebert, 2006;Roth et al, 2010). Given the literature indicating a role for d-GABAA receptors in female stress disorders (Maguire and Mody, 2007;Smith et al, 2007), epilepsy (Mihalek et al, 1999), pain (Peng et al, 2009;Bonin et al, 2011), post-traumatic stress disorder (Wiltgen et al, 2005;Pibiri et al, 2008), schizophrenia (Marx et al, 2006), autism (Olmos-Serrano et al, 2011), major depression (Holm et al, 2010) and potentially alcoholism (Enoch, 2008;Rewal et al, 2009), the need for d-selective tools is clear. Furthermore, it should not be overlooked that a major swathe of the literature, only partly cited above, alluding to the potential therapeutic relevance of d-GABAA receptors has been based on studies with neurosteroids, which are not completely selective for these extrasynaptic receptors (Belelli et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the preclinical data on gaboxadol demonstrating a hypnotic profile in rats (Thakkar et al, 2008) and that the effects of the drug on EEG were blunted in d 0/0 mice (Winsky-Sommerer et al, 2007), it was pursued as a novel treatment for insomnia, reaching phase III clinical development (Wafford and Ebert, 2006;Roth et al, 2010). Given the literature indicating a role for d-GABAA receptors in female stress disorders (Maguire and Mody, 2007;Smith et al, 2007), epilepsy (Mihalek et al, 1999), pain (Peng et al, 2009;Bonin et al, 2011), post-traumatic stress disorder (Wiltgen et al, 2005;Pibiri et al, 2008), schizophrenia (Marx et al, 2006), autism (Olmos-Serrano et al, 2011), major depression (Holm et al, 2010) and potentially alcoholism (Enoch, 2008;Rewal et al, 2009), the need for d-selective tools is clear. Furthermore, it should not be overlooked that a major swathe of the literature, only partly cited above, alluding to the potential therapeutic relevance of d-GABAA receptors has been based on studies with neurosteroids, which are not completely selective for these extrasynaptic receptors (Belelli et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological investigations indicated spinal NR2B subunit phosphorylation is crucial in the induction of cross-organ sensitization (19,20,23). Although the physiological/pathophysiological relevance is still without final proof, cross-organ sensitization was linked to the development of viscero-visceral referred pain in the pelvic area, for it is characterized by pathological enhancement of urethra activity caused by activation of nociceptive afferent fiber arising from visceral organs (24). Therefore, we hypothesize that the interactions between ephrinB2 and EphBRs as well as the downstream intracellular cascade are involved in cross-organ sensitization.…”
mentioning
confidence: 99%
“…Recent evidence suggests that δ-GABA A R play a critical role in central pain sensitization [58,59]. Behavioral characterization of gabrd knockout mice (gabrd−/−) which lack δ subunit, showed that injection of formalin in the hind paw induces a biphasic response, and have reduced formalin phase II response.…”
Section: The Gaba a Receptor Auxiliary Subunitsmentioning
confidence: 99%